PENGARUH NILAI UJIAN SEKOLAH BERSTANDAR NASIONAL TERHADAP PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH MENENGAH PERTAMA - Nuryati Nuryati; Nuni Astriana (Academy of Education Journal, 2020)
Educational assessment is the process of gathering and processing information to determine the achievement of student learning outcomes at the level of primary and secondary education. Assessment is carried out in the spiritual, social, knowledge and skills domains that are carried out in a planned and systematic manner during and after the learning process of a competency of learning content for a certain period of time. The subject of this research is the value of the National Standard School Examination (USBN) and the learning achievement of Bina Jaya Bantul Middle School students with a sample size of 14 students during the study period from April to May 2018. This study was conducted with the aim to find out the magnitude of the effect of USBN scores on learning achievement . The data collection techniques use tests and documentation. Data analysis using validity, reliability, distinguishing problems and the level of difficulty of the questions was done to test the quality of the questions. Documentation is done to get the USBN value data. With descriptive statistical analysis to find out the value of USBN and student achievement. To find out the magnitude of the effect of USBN scores on student achievement in Civics Education subjects is done with a simple regression test, because there is only one independent variable and one dependent variable. Simple regression test results are the regression coefficient 0.942 and R2 = 0.698 with the meaning that the value of the USBN affects learning achievement as much as 69.8% while 30.2% is influenced by factors from outside this study.